Missed opportunities for pneumococcal vaccinations in high-risk and older adults in the United States. Issue 1 (January 2020) - Olasupo, Omotola; Segal, Richard; Brown, Joshua
Abstract: Pneumococcal vaccination rates remain sub-optimal in high-risk adult populations. This analysis quantified "missed opportunities, " defined as number of healthcare encounters in unvaccinated patients who are recommended to be vaccinated. The 2015 National Health Interview Survey was used to assess vaccination status from adults 18–64 with risk factor and adults ≥65 years-old. In older adults, there was a mean of 5.15 (95% CI: 4.90–5.39) healthcare visits that could be opportunities for pneumococcal vaccination. In adults 18–64 years at high risk, there was a mean of 4.83 (95% CI: 4.66–4.99). Healthcare providers should take advantage of patient interactions to increase vaccination rates.